Spatial–temporal trends in forced migrant mortality, 2014–2018 - Till Bärnighausen; Stéphane Verguet; Marcia C Castro; Danielle N Poole; Bethany Hedt-Gauthier (BMJ Global Health)
Introduction The identification of spatial–temporal clusters of forced migrant mortality is urgently needed to inform preventative policies and humanitarian response. As a first step towards understanding the geography of forced migrant mortality, this study investigates spatial–temporal patterns in death at a global scale.Methods We used information on the location and dates of forced migrant deaths reported in the International Organization for Migration’s Missing Migrant Project from 2014 to 2018. Kulldorff’s spatial–temporal and seasonal scans were used to detect spatial–temporal and temporal heterogeneity in mortality.Results A total of 16 314 deaths were reported during the study period. A preponderance of deaths occurred at sea each year (range 26%–54% across 5 years). Twelve spatial–temporal clusters of forced migrant mortality were detected by maximum likelihood testing. Annually, the period of August–October was associated with a 40-percentage-point increase in the risk of mortality, relative to other time periods.Conclusions Death during forced migration occurs close to national borders and during periods of intense conflict. This evidence may inform the design of policies and targeting of interventions to prevent forced migration-related deaths.